Physicochemical Characterization and Screening-Level Treatability Assessment of Institutional Wastewater: A Case Study of Far Western University, Nepal - Hamal, Sagar; Pandit, Shravya Raj (Journal of Engineering Technology and Planning, 2025)
Wastewater produced by educational institutions in low-resource contexts is commonly discharged without treatment, despite the limited availability of empirical evidence describing its composition and treatment potential. In response to this gap, the present study undertakes a physicochemical characterization and a screening-level assessment of the treatability of wastewater generated at the central campus of Far Western University (FWU), Nepal. Grab samples were collected during peak usage periods in the pre-monsoon season from three representative sources: toilet and bathing facilities, canteen activities, and laboratory discharges. Key parameters including pH, total suspended solids (TSS), five-day biochemical oxygen demand (BOD₅), and chemical oxygen demand (COD) were determined in accordance with standard APHA analytical protocols. Wastewater exhibited mildly alkaline conditions, with a mean pH of 8.3 ± 0.63. Average concentrations of TSS (140 ± 35 mg/L), BOD₅ (213 ± 24 mg/L), and COD (453 ± 37 mg/L) substantially exceeded applicable effluent discharge limits, reflecting a high load of suspended solids and biodegradable organic matter. The mean BOD₅/COD ratio of 0.46 ± 0.03 indicates moderate biodegradability and suggests suitability for biological treatment processes, while the TSS/BOD₅ ratio of 0.64 ± 0.08 implies favorable settling behavior and effective potential for primary solids removal. These indicators were interpreted conservatively, acknowledging the inherent limitations associated with single-event grab sampling. Findings indicate that wastewater generated at FWU is predominantly domestic in character but exhibits elevated suspended solids and organic strength. This composition supports a treatment approach involving preliminary and primary solids removal followed by biological processes. While the study provides baseline evidence for an underrepresented institutional setting in western Nepal, extended temporal monitoring, composite sampling, and pilot-scale evaluations are necessary to confirm treatment performance and refine system design parameters.